AYURVEDIC MANAGEMENT OF INFERTILITY - Dr. Pooja Sharma (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2019)
Infertilityis an unsuccessful condition of pregnancy although having normal intercourse over 12months. Multi factors are responsible for femaleinfertility as like stress, Hormonal imbalance, Vata, Visham Agni etc. Ayurveda assures the normalpregnancy through the followingpropermaintenance of life style and also with the help of Ayuvedic medicine and therapies. ChiruvilwadiKashayam, DhanwantharamGulika, Jeerakarishtam, Kumaryasavamand Manasamithravatakamare such good medicines for Infertility. These Aushadhas are beneficial tomaintain Agni, normalize Vata and assure properhealth of mind. These medicines are also work on overall aspect of reproductive organs such as on ovaries, fallopian tubes, Uterus etc. These all are given in starting or first half of cycle for conceives to the patients. During thesecond half of the cycleGarbhasthapanamedicines are beneficial to maintain the stability of Garbh. KEYWORDS–Ayurveda, Vata, Agni Infertility, health.